CULTURAL REFLECTIONS IN OKKY MADASARI'S NOVEL MATA DAN MANUSIA LAUT - Heni Ratnasari; La Ode Sahidin; Marwati (CASA CENDEKIA MEDIA, 2025)
This study aims to describe the cultural reflections in Okky Madasari's novel Mata dan Manusia Laut (Eyes and Sea People). This is a qualitative study using library research as the research method. The data in this study are words, sentences, and texts related to cultural reflections in the novel Mata dan Manusia Laut (Eyes and Sea People) by Okky Madasari. The results show that there are five cultural reflections in Okky Madasari's novel Mata dan Manusia Laut, namely: lifestyle, customs, beliefs, education, and equipment. Based on the results of the research and discussion in Okky Madasari's novel Mata dan Manusia Laut, data related to its cultural reflections were obtained, namely: lifestyle, customs, beliefs, education, and equipment.